The TNFRSF13C H159Y Variant Is Associated with Severe COVID-19: A Retrospective Study of 500 Patients from Southern Italy - Russo, Roberta (Genes (Basel), 2021)
To identify host genetic determinants involved in humoral immunity and associated with the risk of developing severe COVID-19, we analyzed 500 SARS-CoV-2 positive subjects from Southern Italy. We examined the coding sequences of 10 common variable immunodeficiency-associated genes obtained by the whole-exome sequencing of 121 hospitalized patients. These 10 genes showed significant enrichment in predicted pathogenic point mutations in severe patients compared with the non-severe ones. Moreover, in the TNFRSF13C gene, the minor allele of the p.His159Tyr variant, which is known to increase NF-kB activation and B-cell production, was significantly more frequent in the 38 severe cases compared to both the 83 non-severe patients and the 375 asymptomatic subjects further genotyped. This finding identified a potential genetic risk factor of severe COVID-19 that not only may serve to unravel the mechanisms underlying the disease severity but, also, may contribute to build the rationale for individualized management based on B-cell therapy.